Creative Problem Solving (CPS) Learning to Improve Ability an Strudent’s Critical and Creative Thinking on Science Materials - Fahrisa, Nur; Parmin, Parmin (Universitas Negeri Semarang, 2022)
This study aims to determine the effectiveness of using the CPS (Creative Problem Solving) learning model to improve students' critical and creative thinking skills. This research is an experimental study using a quasi-experimental research design with a non-equivalent control group design. The sampling technique used purposive sampling and obtained class VIII A and VIII F. Improving students' critical thinking skills based on T-Test test data pretest and posttest were 4.01 in the control class and 10.29 in the experimental class, both of which were higher than the Ttable, which was 1.99. Improving students' creative thinking skills based on the STUDENT WORKSHEET T-Test Test of 5.035 in the control class and 10,041 in the experimental class, and the T-Test mind mapping of 6,428 in the control class and 6,240 in the experimental class. From the test results, it was found that H0 was rejected so that there was an increase in students' critical and creative thinking skills. Thus, the application of the CPS (Creative Problem Solving) model on the Science material is effectively used to improve students' critical and creative thinking skills.